2014
DOI: 10.1037/a0036553
|View full text |Cite
|
Sign up to set email alerts
|

Social class and academic achievement in college: The interplay of rejection sensitivity and entity beliefs.

Abstract: Undergraduates, especially those from lower income backgrounds, may perceive their social class background as different or disadvantaged relative to that of peers and worry about negative social treatment. We hypothesized that concerns about discrimination based on one's social class (i.e., class-based rejection sensitivity or RS-class) would be damaging to undergraduates' achievement outcomes particularly among entity theorists, who perceive their personal characteristics as fixed. We reasoned that a perceive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(52 citation statements)
references
References 69 publications
(131 reference statements)
2
48
0
Order By: Relevance
“…Study 2, which investigated schools from the merged lower and middle track, showed higher entity endorsement among Turkish-origin students than among Germans. Rheinschmidt and Mendoza-Denton (2014) showed that an entity view interacted with rejection sensitivity based on social class to predict college performance. As Turkish-origin migrants are overrepresented in the lower track as well as the lower social class in Germany (e.g., Matzner, 2012), future research should investigate the interrelation of these variables in predicting outcomes in the German educational context.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Study 2, which investigated schools from the merged lower and middle track, showed higher entity endorsement among Turkish-origin students than among Germans. Rheinschmidt and Mendoza-Denton (2014) showed that an entity view interacted with rejection sensitivity based on social class to predict college performance. As Turkish-origin migrants are overrepresented in the lower track as well as the lower social class in Germany (e.g., Matzner, 2012), future research should investigate the interrelation of these variables in predicting outcomes in the German educational context.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…However, compensating for stereotypic lack of competence, lower-ranked people may instead value their own warmth (trustworthiness, friendliness) [29], as others do [5]. A chronic self-concept of lower competence has a major impact on individuals’ academic aspirations and achievements, especially on those who believe their personal characteristics are fixed (i.e., holding entity beliefs) and are sensitive to class-based rejection [30]. …”
Section: Social-class Stereotypes’ Academic Consequencesmentioning
confidence: 99%
“…Last, student affairs professionals need to consider what impact of the changes and barriers they are experiencing—whether such changes and barriers have led to stressful disequilibrium or smooth transition to equilibrium. According to research, anticipated changes (e.g., expectation of being rejected) in addition to experienced changes can also affect students’ college adjustment (Rheinschmidt & Mendoza‐Denton, ). These considerations will enable student affairs professionals to better understand students’ levels of college adjustment and what resources are further required to help the students.…”
Section: Facilitating Students’ Social Class Identity Developmentmentioning
confidence: 99%